Pendidikan Moderasi Dalam Keluarga: Kristalisasi Beragama Suku Dayak Ngaju - Surawan, Surawan; Rusliana, Waode Gusti; Halis, Nur (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2023)
This research is qualitative with the research subjects being 3 families of the Dayak Ngaju tribe. Data collection techniques were carried out using disguised observation techniques, semi-structured interviews, and documentation. The results of the study show that the implementation of the values of moderation in religion in the Dayak Ngaju family such as the value of tawassuth (taking the middle way) is implied by mutual friendship during major religious celebrations; the value of tawazun (balance) by maintaining harmonious relations between family members; i'tidal values (justice) through mutual respect for one another without any discrimination between family members; the value of tasamuh (tolerance) by giving family members the freedom to embrace their beliefs; the value of musawah (equality) by always being friendly in entertaining family members, Muslim and non-Muslim guests without any discrimination; and the value of shura (deliberation) by building good communication or dialogue between family members.